Fostering children's relationship with nature: exploring the potential of Forest School. Issue 5 (29th July 2018) - Smith, Michelle A.; Dunhill, Ally; Scott, Graham W.
ABSTRACT: Forest School offers children opportunities to explore the natural environment regularly over an extended period of time. It is based on six key principles, one of which states Forest School fosters a relationship with nature and develops long-term pro-environment attitudes through regular personal experiences in nature. We consider to what extent this aim is achieved by exploring the published evidence. We identify that a relationship with nature could be demonstrated under six themes although there is little robust evidence to support this. We suggest further research is carried out directly linked to this aim of Forest School.